The impact of neighborhood environment on the mental health: evidence from China - Lei, Kaiqi; Yang, Jianke; Ke, Xiwang (Frontiers in Public Health, 2025)
IntroductionThe community environment is a significant social determinant affecting individual mental health.PurposeThis study explores the impact mechanisms and urban-rural heterogeneity in the relationship between socioeconomic status and individual mental health, focusing on community environmental perceptions and neighborhood interactions.MethodsThis study used data from the 2021 Chinese General Social Survey (CGSS), selecting a sample of 1,974 respondents. First, a structural equation modeling (SEM) approach was employed for path analysis. Second, a bias-corrected nonparametric percentile bootstrap method was used to test for mediation effects and estimate confidence intervals. Finally, the heterogeneity of the mediation model across urban and rural communities was examined based on community type.ResultsThe results indicate that socioeconomic status is the primary determinant of mental health disparities. The mechanisms of environmental perception and social interaction play significant roles in bridging health disparities between social classes. Moreover, these mediating effects show considerable urban-rural heterogeneity. Specifically, the environmental perception mechanism has a stronger impact on rural residents, while social interaction mechanisms are more pronounced in urban communities.DiscussionThe study emphasizes the importance of addressing environmental pollution and enhancing community social interactions as key strategies to reduce health disparities. Improving ecological governance and fostering community engagement, are essential for narrowing the health gap across socioeconomic groups.